2014
DOI: 10.1093/mnras/stu1910
|View full text |Cite
|
Sign up to set email alerts
|

On the relative ages of the α-rich and α-poor stellar populations in the Galactic halo

Abstract: We study the ages of α-rich and α-poor stars in the halo using a sample of F and G dwarfs from the Sloan Digital Sky Survey (SDSS). To separate stars based on [α/Fe], we have developed a new semi-empirical spectral-index based method and applied it to the low-resolution, moderate signal-to-noise SDSS spectra. The method can be used to estimate the [α/Fe] directly providing a new and widely applicable way to estimate [α/Fe] from low-resolution spectra. We measured the main-sequence turnoff temperature and combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 59 publications
9
30
1
Order By: Relevance
“…One key observable of our Milky Way system is that although its halo population is α-rich (Hawkins et al 2014;Jackson-Jones et al 2014), its (classical) satellites are predominantly α-poor, with an exception for their most metal-poor components (e.g., Shetrone et al 1998Shetrone et al , 2001Shetrone et al , 2003Tolstoy et al 2003;Venn et al 2004;Koch et al 2008;Kirby et al 2010;Starkenburg et al 2013b;Jablonka et al 2015;Frebel & Norris 2015). Several modelling efforts have already pointed out that indeed such a discrepancy could arise in a stellar halo built out of few early-accreted, massive main progenitor galaxies.…”
Section: Relation Between Iron Abundance and Supernovae Type Ia Delaymentioning
confidence: 99%
“…One key observable of our Milky Way system is that although its halo population is α-rich (Hawkins et al 2014;Jackson-Jones et al 2014), its (classical) satellites are predominantly α-poor, with an exception for their most metal-poor components (e.g., Shetrone et al 1998Shetrone et al , 2001Shetrone et al , 2003Tolstoy et al 2003;Venn et al 2004;Koch et al 2008;Kirby et al 2010;Starkenburg et al 2013b;Jablonka et al 2015;Frebel & Norris 2015). Several modelling efforts have already pointed out that indeed such a discrepancy could arise in a stellar halo built out of few early-accreted, massive main progenitor galaxies.…”
Section: Relation Between Iron Abundance and Supernovae Type Ia Delaymentioning
confidence: 99%
“…The chemistry and dynamics are important tools to distinguish different populations. Furthermore, with population ages, the properties of the stellar populations can be understood more comprehensively (e.g., Schuster et al 2012;Haywood et al 2013; Ramírez et al 2013;Hawkins et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With high-resolution spectra, series works, i.e., Nissen & Schuster (2010 and Schuster et al (2012), confirmed that two halo populations exist that are distinguished by element abundances, ages, and orbital parameters. Using a sample of F and G dwarfs from low-resolution SDSS spectra, Hawkins et al (2014) found that the relatively different α-rich and α-poor populations in the Galactic halo have different ages in the metal-rich edge and have identical ages in the metal-poor region. Whether the Galactic disk consists of a thick disk and a thin disk that were formed in different processes is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Each individual spectrum is continuum subtracted using the BMC method of Rogers et al (2010), with the standard choices of a 100 Å box width and a 90% level for the "boosted median." This choice has been comprehensively and independently tested to provide robust estimates of the continuum in SDSS spectra (Hawkins et al 2014). Each line is subsequently fitted by a function In order to remove spurious pixels, we mask those flagged as bad pixels by the SDSS pipeline.…”
Section: Determination Of the Centroids Of Spectral Linesmentioning
confidence: 99%